(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
When it comes to the deprivation of the compulsory portion for the benefit of the descendants, is perceived in a certain sense the presence of the relationship between the freedom that the testator has in terms of testing, ie the freedom of testing and the compulsory portion. The deprivation of the compulsory portion in the favor of the descendants (exheredatio bona mente) appears as a dispositive act of the testator who in a way has a protective character towards the descendants. Namely, the aim of the paper is to perceive the protective character of this institute, to perceive its significance as a sanction with a certain punitive element. In the paper, we also elaborate on the status of the gifts made by the testator during his lifetime to the deprived descendant. Furthermore, the paper explains the reasons that lead to the possibility of the testator to deprive the heir of the compulsory portion, the scope of that deprivation, and of course the very notion of deprivation is explained, clarifying the theoretical dilemmas regarding such deprivation. Given this, the paper in addition to its theoretical dimension, it also gains its practical importance, important for the popularization of this institute.